Intelligent control systems of electrical complexes in biotechnological objects - Lysenko, Vitaliy; Dudnyk, Alla (Lviv Polytechnic Publishing House, 2015)
The aim of this paper is to substantiate efficiency of creation automation control system in a greenhouse with using solar radiation intensity and temperature predictions by neural networks.
Keywords: control system; biotechnical object; electrical complex; neural network; forecasting; greenhouse; poultry farm